Delivery of Vaccinia Virus Complement Control Protein (VCP) and Curcumin to the rodents' brain : implications in Alzheimer's disease and HIV dementia - Kulkarni, Amod Prakash (Division of Clinical Pharmacology, 2014)
Includes abstract. Includes bibliographical references (p. 245-262).